ENHANCING COLD MIX ASPHALT PERFORMANCE WITH GEOPOLYMER TECHNOLOGY - Falah Hasan Ali; Taher M. Ahmed (Mağallaẗ Al-kūfaẗ Al-handasiyyaẗ)
Generally, Cold asphalt emulsion mixtures (CAEM) produced and compacted at ambient temperatures. The main objective of this study is to investigate the improvement of the performance for mixtures by the addition of geopolymers based on cementitious material by preparing the asphalt samples using three concentrations of geopolymer utilized as a substitute for limestone filler (LF),The mechanical properties of the mixtures were evaluated using the Marshall test, Indirect Tensile Strength (ITS) test, Kim test and Water sensitivity test TSR. The test results revealed that the concentration of (NaOH) has a substantial influence on the structure and characteristics of geopolymers, enhancing Marshall stability, ITS, and rut resistance. CAEM with geopolymer considerably improved Marshall stability and deformation resistance especially those containing fly ash.CAEM with geopolymer provides larger ITS conditioning and a TSR over 100% better than hot mix asphalt HMA. Furthermore, it is noteworthy to mention that the addition of geopolymer has somewhat improved the mechanical properties and durability characteristics of the CAEM.